THE ALORESE LANDSCAPE TERMINOLOGY: FORM, FUNCTION, AND SEMANTIC REFERENCES IN AN AUSTRONESIAN LANGUAGE IN EAST INDONESIA - Sulistyono, Yunus (UIN Raden Mas Said Surakarta, 2023)
This paper aims to describe the landscape and seascape terminology of Alorese, an Austronesian language spoken in the Alor archipelago of eastern Indonesia. Alorese uses unique way of expressing landscape terminology by retaining some of its ancestral Austronesian landscape terminology and innovating relatively new forms, functions and semantic references from its neighboring non-Austronesian languages. Previous research show that Alorese has innovated relatively new forms due to contact with its surrounding non-Austronesian languages. The current paper fills the gap where there has not been any discussion regarding the Alorese landscape terminology outside its preposition function. Discussion on cross-linguistic categorization, such as landscapes in areas such as eastern Indonesia is proven to be fruitful. The Alorese linguistic landscapes are expressed through geographical references and some forms appear unique to Alorese's dialectal variations. In general, the reference to elevations and directionalities in Alorese is achieved through geographical references, such as nala kokar ‘towards Kokar (a town)’ or klou lau ‘seawards (lau 'sea')’ rather than generic land form terms, suchas wara ‘westwards’ which is also an Indonesian loan barat ‘west’. Its non-Austronesian borrowed terminologies include words, such as iti dola ‘mountainwards’, containing loanwords from Alor-Pantar (Papuan) languages dol ‘mountain’. The data of this research were gathered from my 2018 and 2020 fieldwork in 14 Alorese villages located across the northern coast of Alor and Pantar as well as the small islands of Buaya and Ternate. Collections of terminologies show variations in the use of words not only depending on the geographical references, but also relative to the neighboring non-Austronesian languages.